Islamic Biomedical Ethics: Principles and Application by Abdulaziz Sachedina (New York: Oxford University Press, 2009. 280 pages.) (American Journal of Islam and Society, 2009)
Immediately distinctive of Sachedina’s approach to biomedical ethics is hisconception of the Shari`ah as an integrated legal-ethical tradition: TheQur’an provides jurists with moral underpinnings of religious duty, and thegrounding texts are to be taken as an ethical standard of conduct. Legal rulingsare to be extracted accordingly. In short, the Islamic juridical tradition(usul al-fiqh) presupposes ethics.Sachedina argues for an ethical foundation – a strong epistemologicalclaim– and concerns himself with conceptual bases ofmoral reasoning ratherthan with juridically derived judgment per se. He elucidates deontologicalteleologicalprinciples that are “cross-culturally communicable” yet appreciativeof “situational exigencies.” In contrast to the juridical objective ofissuing legal opinions (fatwas), bioethical pluralism motivates Sachedina’spreference for recommended moral conduct (tawsiyah). He therefore movesaway from the tendency of some scholars to conceive of bioethics merely as“applied Islamic jurisprudence.”The author’s epistemic and hermeneutic commitment commends hiswork, given the two facts that he identifies: (1) informed public debate oncritical issues of biomedical ethics within Islam is lacking, relative to thedegree of democratic governance, and (2) the epistemological and ontologicalbases of ethical inquiry remain underdeveloped in the Muslim seminariancurriculum. Consequently, there is a critical need to demonstrate toreligious scholars that Islamic ethics have much in common with secularbioethics and thus that an opportunity for dialogue exists ...